2019
DOI: 10.1016/j.mito.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ modulation rescues mitochondrial fatty acid oxidation defects in the mdx model of muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a recessive, fatal X-linked disease that is characterized by progressive skeletal muscle wasting due to the absence of dystrophin, which is an a essential protein that bridges the inner cytoskeleton and extra-cellular matrix. This study set out to characterize the mitochondria in primary muscle satellite cell derived myoblasts from mdx mice and wild type control mice. Compared to wild type derived cells the mdx derived cells have reduced mitochondrial bioenergetics and have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
4
13
0
Order By: Relevance
“…Percival et al reported a reduction in the density of the subsarcolemmal mitochondria pool in mdx TA muscle(80), and mdx-derived myoblasts contain fewer mitochondria than their WT counterparts(81), consistent with this hypothesis.Upstream regulator analysis identified multiple master regulators of mitochondrial biogenesis as being perturbed in dystrophic muscle. These included the peroxisome proliferator activated receptor family members: PPARA, PPARG, and PPARD, their associated transcriptional coactivators: PPARGC1A (PGC-1α), and PPARGC1B (PGC-1β), and the mitochondria-specific transcription factor TFAM(Figure 4, S10C, S12).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Percival et al reported a reduction in the density of the subsarcolemmal mitochondria pool in mdx TA muscle(80), and mdx-derived myoblasts contain fewer mitochondria than their WT counterparts(81), consistent with this hypothesis.Upstream regulator analysis identified multiple master regulators of mitochondrial biogenesis as being perturbed in dystrophic muscle. These included the peroxisome proliferator activated receptor family members: PPARA, PPARG, and PPARD, their associated transcriptional coactivators: PPARGC1A (PGC-1α), and PPARGC1B (PGC-1β), and the mitochondria-specific transcription factor TFAM(Figure 4, S10C, S12).…”
mentioning
confidence: 76%
“…Notably, many of the regulatory proteins identified above have been explored as potential targets for pharmacological manipulation (Figure 9). For example, PGC-1α gain-of-function and pharmacological activation of PPARD have been shown to be beneficial in the mdx mouse (98), and reverse mitochondrial defects in mdx myoblasts (81), respectively. Activation of AMPK and SIRT1 (by AICAR (99) and resveratrol (100) respectively) has been shown to attenuate pathology in the mdx mouse, also a likely consequence of PGC-1α up-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1α is reported to be a direct target of PPARδ in the skeletal muscle (Phua et al, 2018). Recently, Bell et al (2019) showed that PPARδ improves mitochondrial function in the mdx mice. We also investigated the mitochondrial respiratory complexes (I, II, III, IV, and V), and similar to the PGC-1α and PPARδ results, the levels of these complexes were up regulated in exercise-trained-mdx mice treated with Tempol.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, mitochondrial dysfunction has been shown to occur before the onset of myofiber necrosis, muscle wasting and myofibrillar defects [253]. Impaired substrate utilization and ATP synthesis have been reported in dystrophic mitochondria [254,255]. There occurs an uncoupling in the process of mitochondrial oxidative phosphorylation during the progression of muscular dystrophy [256,257].…”
Section: Mechanisms Of Subcellular Ca 2+ -Handling Abnormalities In Dystrophic Musclementioning
confidence: 99%